2015
DOI: 10.3838/jjo.64.77
|View full text |Cite
|
Sign up to set email alerts
|

Population and habitat of wintering Brent Geese <i>Branta bernicla</i> in eastern Oshima Peninsula, Tsugaru Strait and Mutsu Bay

Abstract: Abstract. The population and habitat of Brent Geese Branta bernicla were investigated in the species main wintering area in Japan (around the Tsugaru Strait) in late December 2012. A total of 1,060 individuals was found, most of which occurred in southeast Oshima Peninsula and southeast Mutsu Bay. Goose density was higher in areas with artificial revetments and rocky shore, where marine algae (the main diet of the geese) grow easily. Coastlines with offshore structures were selected as feeding habitat because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, our study showed that some geese occurred in unprotected areas along the north coast of the Nemuro Peninsula. Geese frequently forage in sites with artificial structures in unprotected areas (Shimada et al 2013;Hirata et al 2015). The potential threats of habitat destruction and deterioration persist in these unprotected areas.…”
Section: ) Distribution and Habitat Use Of Stopover Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study showed that some geese occurred in unprotected areas along the north coast of the Nemuro Peninsula. Geese frequently forage in sites with artificial structures in unprotected areas (Shimada et al 2013;Hirata et al 2015). The potential threats of habitat destruction and deterioration persist in these unprotected areas.…”
Section: ) Distribution and Habitat Use Of Stopover Sitesmentioning
confidence: 99%
“…Several studies have been made of the wintering ecology of Brent Goose in East Asia (e.g. Shimada et al 2013;Hirata et al 2015). Shimada et al (2013) reported that the geese showed seasonal changes in their habitat use in relation to the availability of food such as sea grass in fishing harbors and attached to fishery rafts in coastal areas.…”
mentioning
confidence: 99%